On the evolution of pore microstructure during coal char activation with steam/CO2 mixtures. (March 2020) - Maya, Juan C.; Macías, Robert; Gómez, Carlos A.; Chejne, Farid
Abstract: The present work develops a novel mathematical model for coal char activation with CO2, steam, and a CO2 /steam mixture. The main assumption is that CO2 and steam react with distinct active sites, considered by attributing a unique char structure effect to each gasifying agent; the CO2 -char reaction increases the pore length, whereas the steam-char reaction increases the pore radius. Additionally, pore overlapping effect was taken into account and the radial pore growth was computed by means of a population balance equation. Model predictions of both the pore size distribution and specific surface area changes were compared with experimental data, resulting in an outstanding fit. This supports the model main assumption, which reconciles discrepancies between various authors regarding the overall reaction rate during activation of coal chars with CO2 /steam mixtures. Finally, the maximum specific surface area occurs under chemically-controlled conditions, where all particle zones reach their maximum surface areas simultaneously, while for activation with diffusional limitations each particle zone attains its maximum specific surface area at a different time. Graphical abstract: Image 10006